Drought Assessment of Yeşilırmak Basin Using Long-term Data - Kartal, Veysi (Fırat Üniversitesi, 2024)
Drought is a prolonged period of inadequate rainfall, such as one season, one year or several years, on a statistical multi-year average for a region. Drought is a natural disaster effective on several socio-economic activities from agriculture to public health and leads to deterioration of the environment sustainability. The drought starts with meteorological drought, continues with agricultural and hydrological drought, and when it is in the socioeconomic dimension, the effects begin to be observed. Generally, drought studies are based on drought indices in the literature. This study applied long-term precipitation, temperature, and evaporation data from Samsun, Tokat, Merzifon, Çorum and Amasya meteorological stations from 1961 to 2022 to investigate the drought in the Yeşilırmak basin of Turkey. The present study applied Standardized Precipitation Index (SPI), and Effective Drought Index (EDI), China Z- Index (CZI) and Standardized Precipitation Evapotranspiration Index (SPEI) based on daily, monthly, seasonal, and annual time periods to evaluate drought. The Sen slope and Mann-Kendall test were employed for data analysis. The results revealed that the monthly drought indices for the study area were almost identical for the study area. Although dry and wet periods were observed.

Kuraklık, tarımdan halk sağlığına kadar birçok sosyo-ekonomik faaliyeti etkileyen ve çevrenin sürdürülebilirliğini bozulmasına neden olan doğal bir afettir. Kuraklık meteorolojik kuraklıkla başlar, tarımsal ve hidrolojik kuraklıkla devam eder, sosyoekonomik boyuta geçtiğinde ise etkileri görülmeye başlar. Literatürde genellikle kuraklık çalışmaları kuraklık indekslerine dayandırılmaktadır. Bu çalışmada, Türkiye'nin Yeşilırmak havzasındaki kuraklık özelliklerini incelemek için 1961-2022 yılları arasında Samsun, Tokat, Merzifon, Çorum ve Amasya meteoroloji istasyonlarından elde edilen uzun süreli yağış, sıcaklık ve buharlaşma verileri kullanılmıştır. Bu çalışmada, kuraklığı değerlendirmek için aylık, mevsimlik ve yıllık zaman dilimleri kullanılarak günlük verilere dayalı CZI, SPEI, SPI ve EDI değerleri elde edilmiştir. Veri analizi için Sen eğimi ve Mann-Kendall testi kullanılmıştır. Sonuçlar, çalışma alanı için aylık kuraklık indekslerinin neredeyse aynı olduğunu ortaya koymuştur. Özellikle şiddetli ve yağışlı dönemler gözlemlenmiş olmasına rağmen, genel olarak normal kuraklık seviyeleri gözlenmiştir
Yeşilırmak Havzası'nın Uzun Vadeli Veriler Kullanılarak Kuraklığının Değerlendirmesi
Keywords: Water Resources Engineering; Su Kaynakları Mühendisliği